Comparison of Intergrowth-21st and Fenton growth standards to evaluate and predict the postnatal growth in eastern Chinese preterm infants - Lan, Siyuan; Fu, Huanhuan; Zhang, Chengchen; Chen, Yuyun; Pan, Liya; Song, Siqing; Wang, Yizhi; Hong, Li (Frontiers in Pediatrics, 2023)
Objectives: To compare the differences between Intergrowth-21st (IG-21) and Fenton growth standards in the classification of intrauterine and extrauterine growth restriction (EUGR) in eastern Chinese preterm infants, and detect which one can better relate to neonatal diseases and predict the physical growth outcomes at 3-5 years old. Methods: Premature infants admitted to a tertiary pediatric hospital in Shanghai, China from 2016 to 2018 were enrolled. Prenatal information, neonatal diseases during hospitalization, and anthropometric data (weight, height, and head circumference) at birth and at discharge were collected and analyzed. Physical growth outcomes (short stature, thinness, and overweight) were examined by telephone investigations in 2021 at age 3-5 years. Results: The medium gestational age and birth weight of the included 1065 preterm newborns were 33.6w and 1900g, respectively. The IG-21 curves diagnosed more newborns with small for gestational age (SGA) (19% vs. 14.7%), and fewer newborns with longitudinal EUGR on height (25.5% vs. 27.9%) and head circumference (17.9% vs. 24.7%) compared to Fenton curves. Concordances between Fenton and IG-21 standards were substantial or almost perfect in the classification of SGA and longitudinal EUGR, but slight in cross-sectional EUGR. EUGR identified by Fenton curves was better related to neonatal diseases than IG-21 curves. There were no statistical significances in the prediction of short stature, thinness, and overweight at 3-5 years old between the two charts. Conclusions: IG-21 growth standards are not superior to Fenton in assessing preterm growth and development in the eastern Chinese population.